Characterization of aroma compounds present in an industrial recovery concentrate of coffee flavour (2018)
ABSTRACT: In this study, the odour-active volatile compounds present in a coffee aroma concentrate obtained from a soluble coffee extract in an industrial aroma recovery system based on distillation and evaporation were characterized by solid-phase microextraction coupled to gas chromatography with mass spectrometry and olfactometric detection technique. This analysis allowed the identification of 58 compounds, of which 15 pyrazines, 9 furans, 6 aldehydes, 4 ketones, 4 esters, 4 pyrroles, 4 sulphur compounds, 3 pyridines, 3 phenols, 3 alcohols, an oxazole, and a pyran are highlighted. From these families, the following compounds presented the highest sensory activities (%MF = 100): 2-methylbutanal, 2-methyl-2-butenal, 2-furancarboxaldehyde, furfural, and methyl phenyl acetate. These compounds can be considered as quality markers in the process control on the aroma recovery system.